Reading: a meaningful way to promote learning english in high school (2005)
This project involved three different groups of seventh grade, at the Luis López de Mesa state school in Bosa, Bogotá (Colombia). Thinking of a way to adapt the foreign language learning-teaching process to our real conditions, we found reading very useful to enable students to learn English more easily and accurately. We show how English language learning can be developed from reading processes involving the other language skills and can help students to develop individual and social skills. We conclude that reading becomes a meaningful way to learn a foreign language when teachers choose reading material according to learners’ interests, age and needs, and other content areas. Key words: Reading, English language, meaningful reading, action research Este proyecto involucró tres grupos diferentes de estudiantes de grado séptimo del colegio Distrital Luis López de Mesa en Bosa, Bogotá (Colombia). Pensando en una manera de adaptar el proceso de enseñanza-aprendizaje de un idioma extranjero a nuestras condiciones reales, encontramos que la lectura es muy útil para que los estudiantes aprendan inglés de manera más fácil y precisa. Mostramos cómo se puede desarrollar el aprendizaje del inglés a partir de la lectura involucrando las otras habilidades del lenguaje y ayudando a los estudiantes a desarrollar habilidades individuales y sociales. Concluimos que la lectura es una forma significativa de aprender una lengua extranjera cuando los profesores eligen el material de acuerdo con los intereses, edades y necesidades de los estudiantes, y otras áreas del conocimiento. Palabras claves: Lectura, lengua inglesa, lectura significativa, investigación-acción